Pengaruh Penggunaan Teknik Mind Mapping Terhadap Keterampilan Menulis Resensi Novel Siswa Kelas XI SMAN 1 Sungai Lala - Sri Mulyani Rusli (Jurnal Ilmiah Langue and Parole, 2020)
Backgrounds of this research were that first, student could not master the novel review material, second; students were difficult to develop ideas in writing, third; learning media at the school did not support the lesson such as limited projector; fourth, students were bored with the given materials by using a tutor method. The research was to describe the student novel review writing skill before implementing mind mapping technique; second, to describe the student novel review writing skill after implementing mind mapping technique; Third,to describe the effect of mind mapping technique usetowards student novel review writing skill at XI class SMAN 1 Sungai Lala, Indragiri Hulu Regency. The research shows that, first, the average score of student novel review writing skill before implementing mind mapping technique is 61.11 on the range 56-65% and in the moderate qualification (C).Second, the average score of student novel review writing skill after implementing mind mapping technique is 80.73 on the range 86-95% in a very good qualification. Third, there is a significance effect of mind mapping technique usetowards student novel review writing skill at XI class SMAN 1 Sungai Lala, Indragiri Hulu Regency because t count> t table (6.00>1.70).